Pengaruh Strategi Active Learning Tipe Index Card Match terhadap Hasil Belajar Peserta Didik pada Pembelajaran Tematik Terpadu Kelas III Sekolah Dasar - Purwati, Nining; Yunisrul, Yunisrul (Universitas Negeri Padang, 2022)
This study aims to determine the effect of the index card match type active learning strategy on student learning outcomes in integrated thematic learning. This type of research is quasi-experimental with nonequivalent control group design. The research was conducted in 02 Balai Nan Duo in Payakumbuh. The sampling technique is simple random sampling, which is selected as the sample class is class IIIC as the experimental class and class IIIA as the control class. Sampling is using purporsive sampling technique. The instrument used to collecting data in this research is objevtive test with multiple choice form. Based on the results of data analysis using t-test, obtained tcount = (2,92) > ttabel (1,69) at a significant level of 0.05. It means that tcount > ttable, so H1 is accepted. Thus, there is a significant effect of index card macth type active learning strategy on the learning outcomes of integrated thematic in class III of Elementary School.